The use of eggshell as partial sand replacement - Ahmad Nazif Naim, Zali (2015)
Nowadays, construction industries have been commonly used concrete. However, the demand quantity of concrete increased due to the rapid infrastructure development. It is necessary to explore alternative way for overcome this demand such as using the waste material in concrete mixture. Eggshell is one of the waste materials. Therefore, one research the use of eggshell as a partial replacement in concrete mixture was conducted. The purpose of this research to develop concrete using the waste material as well as controlling the environmental pollution by replacing eggshell with the sand in the concrete mixture. The replacement of eggshell used in the concrete making are 5%, 10% and 15% by substitute the sand in order to determine the optimum percentage and characteristic of concrete beam compressive strength. The data collected show the cover strength development. The results showed that the 5% of eggshell replacement was excellent where the compressive strength of sample was higher than control concrete. Then, the others percentage of eggshell replacement were lower of compressive strength than the control concrete.